Complex Permittivity of Materials at Broadband Frequency using Transmission Phase Shift Method - Chan, Yi Lin; Esa, Fahmiruddin; You, Kok Yeow; Abdul Kahar, Rosmila; Abbas, Zulkifly (Journal of Science and Technology, 2017)
This paper reports determination of complex relative permittivity Â of non-magnetic samples Â Teflon, Nylon and Epoxy via transmission phase shift method. The transmission phase shift method offers calibration independent and invariant position features. In this work, a Coaxial Cavity Test Fixture (CCTF) with dimension of 1.8 and 4.1 mm for inner and outer conductor, respectively was customized based on impedance matching theory to study broadband scattering in the range of frequency 1-18 GHz. Impedance matching and cable calibration were performed to reduce the measurement error of scattering parameters; reflection and transmission . Magnitude and phase of Â and Â were measured by vector network analyzer (VNA). The measured phase of Â ( ) for all samples under test were linearized using the MATLAB â€œunwrapâ€ command for further calculation of . The phase shift in Â between with and without sample inside the cavity was detected and it was used to determine for each material under test. The average value of dielectric constants for Teflon, Nylon and Epoxy were 2.11, 2.42 and 3.05, correspondingly for the selected frequency 2, 4, 6, 8, 10, 12 and 14 GHz. While, the average of dielectric losses Â for Teflon and Epoxy were almost overlapped which the values were 0.001 and 0.002, respectively that were higher than that of Nylon at 0.0006. The calculated values are comparable with the theoretical values with small absolute errors. These results suggested that this transmission phase shift method using CCTF was equally consistent when compared to the other techniques used for the determination of and .